Actinometric study of oxygen dissociation in ICP source - Dakhov, A.N.; Dudin, S.V. (Вопросы атомной науки и техники, 2014)
Results of actinometric study of oxygen dissociation in ICP source are presented. For atomic oxygen the emission lines of 844.6 nm was chosen having low impact of dissociative excitation. Actinometer gas in the experiments was argon, with emission line of 750.4 nm. Measurements of the degree of oxygen dissociation were conducted depending on the RF power supplied to the ICP source as well as on the oxygen gas pressure. The dissociation degree varies from few percent to 40 % depending on gas pressure.